2018
DOI: 10.1920/re.ifs.2017.0138
|View full text |Cite
|
Sign up to set email alerts
|

Problem debt and low-income households

Abstract: The Joseph Rowntree Foundation has supported this project as part of its programme of research and innovative development projects, which it hopes will be of value to policymakers, practitioners and service users. The facts presented and views expressed in this report are, however, those of the authors and not necessarily those of the Foundation. Neither are the views expressed necessarily those of the other individuals or institutions mentioned here, including the Institute for Fiscal Studies, which has no co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The alternatives for the financially excluded are few or nonexistent. Our results confirm the importance in the UK of credit over savings to cope with financial insecurity (Hood, Joyce, and Sturrock 2018), with only 22 percent of UK adults not holding credit of any kind in 2017 (Financial Conduct Authority 2018). These results also align well, given the sociodemographic characteristics of our participants, with the fact that 24 percent of UK adults had less than £1,000 as a savings buffer in 2017 (Financial Conduct Authority 2018).…”
Section: Discussion and Conclusion: Until Debt Do Us Part?supporting
confidence: 74%
“…The alternatives for the financially excluded are few or nonexistent. Our results confirm the importance in the UK of credit over savings to cope with financial insecurity (Hood, Joyce, and Sturrock 2018), with only 22 percent of UK adults not holding credit of any kind in 2017 (Financial Conduct Authority 2018). These results also align well, given the sociodemographic characteristics of our participants, with the fact that 24 percent of UK adults had less than £1,000 as a savings buffer in 2017 (Financial Conduct Authority 2018).…”
Section: Discussion and Conclusion: Until Debt Do Us Part?supporting
confidence: 74%
“…In Britain, younger individuals are more likely than older individuals to live in a household with debt with 60–70% of those aged 20–30 living in a household with debt compared to only 39% of those aged 60–64 and only 11% for those aged 80 to 84 (Hood et al, 2018 ). As income increases, so does the prevalence of debt; research shows among among individuals in the lowest income decile, 7% live in households with debts higher than 10,000 euros, and this value increases to 18% among those of the highest income decile, where more than 60% of unsecured debt are held by above-average incomes (Hood et al, 2018 ). Some studies that relate age to debt found that credit card debt peaks among individuals aged 40–49 (Drentea, 2000 ).…”
Section: Introductionmentioning
confidence: 99%
“…One interviewee had gone through "a bit of a stage of buying loads of stuff" due to mental health issues. Unpaid bills and arrears were more often reported than loans or credit card debt, overdrafts and informal borrowing from family members also featured and a number of interviewees had used (sometimes multiple) doorstep, payday or unspecified lenders (see Hood et al, 2018). Social security issues could lead to debt through advances, budgeting loans or crisis loans as well as overpayment.…”
Section: Debtmentioning
confidence: 99%
“…The amount of money owed, when stated, varied dramatically, from a few hundred pounds to £25,000, but interviewees tended to assess the precarity of their position on the basis of whether they could meet their weekly or monthly repayments or how vigorously they were pursued by their creditors rather than the total debt (see Hood et al, 2018). Younger females were particularly likely to disclose fears about visits from bailiffs and in one case an incident in which the interviewee's property was damaged in the course of a dispute with a "friend" or "loan shark" to whom she owed money.…”
Section: Debtmentioning
confidence: 99%